1998
DOI: 10.1080/10473289.1998.10463685
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Environmental Tobacco Smoke Generated by Different Cigarettes

Abstract: A method was developed to reproducibly measure environmental tobacco smoke (ETS) components generated by different cigarettes. Measurements were carried out in an unventilated, controlled environment chamber. True ETS (the aged and diluted combination of exhaled mainstream plus sidestream smoke) was generated by human smokers. To reliably quantitate components normally present at trace levels, the comparisons were carried out at elevated ETS concentrations-greater than 40 times those typically encountered in "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Previous studies have shown that the environmental aerosols emitted by heated tobacco products have much less impact on an indoor environment than ETS generated by smoking cigarettes (Forster et al 2018;Frost-Pineda et al 2008;Ichitsubo and Kotaki 2018;Mitova et al 2016;Nelson et al 1998;Prodanchuk et al 2017;Protano et al 2016Protano et al , 2017Ruprecht et al 2017;Schober et al 2018;Tricker et al 2009). This is to be expected, because on the one hand, the aerosol formation of the heated tobacco products does not involve tobacco combustion or high-temperature pyrolysis, leading in turn to a significant reduction in the generation of HPHCs.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have shown that the environmental aerosols emitted by heated tobacco products have much less impact on an indoor environment than ETS generated by smoking cigarettes (Forster et al 2018;Frost-Pineda et al 2008;Ichitsubo and Kotaki 2018;Mitova et al 2016;Nelson et al 1998;Prodanchuk et al 2017;Protano et al 2016Protano et al , 2017Ruprecht et al 2017;Schober et al 2018;Tricker et al 2009). This is to be expected, because on the one hand, the aerosol formation of the heated tobacco products does not involve tobacco combustion or high-temperature pyrolysis, leading in turn to a significant reduction in the generation of HPHCs.…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3] In addition, it has been shown that each increase of 10 mg/m 3 in ambient PM levels carries a short term health burden that can be calculated in terms of morbidity and mortality, 4 and is perceived as a serious threat by lay persons and decision makers. Accordingly, official annual average PM limits have been set at 40 mg/m 3 for PM 10 in Europe, and at 15 mg/m 3 for PM 2.5 in the USA.…”
mentioning
confidence: 99%
“…8 9 This knowledge can be used to develop an educational message on smoking prevention based on indoor versus outdoor pollution, an issue of concern also for the tobacco industry, as disclosed by the attempts to produce cigarettes with low PM emissions. 10 An additional message could derive from the comparison between PM production by cigarettes and by the new low emission cars. It has been estimated that older gasoline vehicles and light duty diesel emission rates are on average 100 times higher than those of newer vehicles, and that cars and trucks manufactured from 1991-1996 currently account for only 3.8% of PM pollution, as compared to 26.8% caused by cars built from 1986-1990.…”
mentioning
confidence: 99%
“…Spengler et al, 1981;Quackenboss et al, 1989;Neas et al, 1994). In addition to the contribution to the mass concentrations of indoor particles, cigarette smoke is of concern because of the mutagens, carcinogens, and toxic air contaminants that are emitted (Löfroth et al, 1991;Chuang et al, 1991;California Environmental Protection Agency, 1997;Nelson et al, 1998). Thus, a variety of both gaseous and particulate polycyclic aromatic hydrocarbons (PAH) and compounds (PAC) have been identified in buildings with cigarette smoke (Offermann et al, 1991;Mitra & Ray, 1995).…”
Section: Particlesmentioning
confidence: 99%
“…It is interesting that emissions of organics associated with the use of washing machines are decreased when the machine is operated with clothes inside (Howard and Corsi, 1998). Of course, activities such as smoking result in enhanced levels not only of nicotine (e.g., Thompson et al, 1989) but also of a variety of other gases associated with cigarette smoke (e.g., California Environmental Protection Agency, 1997; Nelson et al, 1998). For example, using 3-ethenylpyridine as a marker for cigarette smoke, Heavner et al (1992) estimated that 0.2-39% of the benzene and 2-49% of the styrene measured in the homes of smokers was from cigarette smoke.…”
Section: Volatile Organic Compounds (Vocs)mentioning
confidence: 99%